Ecodesign Criteria For Composite Materials And Products - Attaf, B. (University of Eloued جامعة الوادي, 2013)
According to sustainable development principles, the design of a composite product must be in compliance with the new regulations and standards in terms of Health protection (H) and Environmental preservation (E) besides Quality assurance (Q). With this argument as an objective, our contribution aims to innovate and develop new methodologies providing sustainable design of new generation of composite products through the consideration of the three balanced key aspects: H, E and Q. To achieve these requirements, we have defined and developed new criteria in the form of eco-coefficients, which can later on be implemented into mechanical characterization tests, in advanced composite formulations and associated constitutive equations. They can also be integrated into future finite-element computer programs to assess and improve the performance of the H-E-Q interrelated function.
Articale in Journal of fundamental and Applied Sciences Vol. 05 N. 01
Keywords: composite materials; eco-factor; probability risks, sustainable development; case studies.